Executive function after risk-reducing salpingo-oophorectomy in BRCA1 and BRCA2 mutation carriers: does current mood and early life adversity matter?. Issue 7 (July 2020) - Shanmugan, Sheila; Sammel, Mary D.; Loughead, James; Ruparel, Kosha; Gur, Ruben C.; Brown, Thomas E.; Faust, Jessica; Domchek, Susan; Epperson, C. Neill
Abstract: Objective: Despite the fact that negative mood and executive dysfunction are common after risk-reducing salpingo-oophorectomy (RRSO), occurring in up to a third of women, little is known about risk factors predicting these negative outcomes. Adverse childhood experiences (ACE) predict poorer health in adulthood and may be a risk factor for negative outcomes after RRSO. Given the complex relationship between early life stress, affective disorders, and cognitive dysfunction, we hypothesized that ACE would be associated with poorer executive function and that mood symptoms would partially mediate this relationship. Methods: Women who had undergone RRSO were included in the study ( N = 552; age 30-73 y). We measured executive function (continuous performance task, letter n-back task, and Brown Attention Deficit Disorder Scale Score), exposure to early life stress (ACE questionnaire), and mood symptoms (Hospital Anxiety and Depression Scale). Generalized estimating equations were used to evaluate the association between ACE and executive dysfunction and the role of mood symptoms as a mediator in this relationship. Results: ACE was associated with greater severity of subjective executive dysfunction (adjusted mean difference [aMD] = 7.1, P = 0.0005) and worse performance on both cognitive tasks (continuous performance task: aMD = –0.1, P = 0.03; n-back: aMD = –0.17, P = 0.007). Mood symptoms partially mediated ACE associations with sustained attention (21.3% mediated; 95% CI: 9.3%-100%) and subjective report of executive dysfunction (62.8% mediated; 95% CI: 42.3%-100%). Conclusions: The relationship between childhood adversity and executive dysfunction is partially mediated by mood symptoms. These data indicate that assessing history of childhood adversity and current anxiety and depression symptoms may play a role in treating women who report cognitive complaints after RRSO. N/A: Video Summary: http://links.lww.com/MENO/A571 . Abstract : Supplemental Digital Content is available in the text